Avaliação global-local da vida em fadiga da ponte de Eastingdon - Laura Araujo Nogueira (2023)
Fatigue is one of the main causes of failure in steel structures, and can be understood as a localized and progressive process of damage accumulation, resulting from repetitive loading applications. A large number of old steel bridges existing around the world motivate the investigation of the fatigue performance of these structures. Regarding old and riveted bridges, one should also consider the fact that the construction of these structures is associated with numerous uncertainties, since they were designed for traffic and environmental conditions different from the current ones. In this context, the reinforcement of steel structures becomes essential, with the use of FRP (fiber-reinforced polymers) being a solution to be analyzed to increase fatigue life. Furthermore, in view of the fact that replacing the existing infrastructure in a comprehensive manner is not feasible for economic reasons, the development of techniques for assessing, inspecting, maintaining and recovering these structures emerges as a niche of high interest to the academic community and to the companies that operate in the sector. In this sense, local approaches are important tools in the evaluation of life in fatigue, since they consider in detail the geometry and geometric and material nonlinearities, used from a global model of the structure under study. Therefore, this work aims to study, from a global-local analysis, the fatigue life of the Eastingdon bridge, located in the United Kingdom, using the ANSYS and ABAQUS softwares. The global model is partially developed in the study by Mohabeddine (2019), but it has been refined to allow a later local assessment of critical links. The critical connections identified will be reinforced with FRP (fiber reinforced polymers) and a new assessment of fatigue strength will be performed for comparison purposes. This dissertation is part of a sequence of research carried out within the scope of the European Research Project “FiberBridge”, with the end result of the elaboration of a complete methodology for the reinforcement of steel bridge structures with FRPs, covering from the assessment of life to residual until determining the increase in useful life from the installation of the reinforcement.